Black Ginseng Extract Suppresses Airway Inflammation Induced by Cigarette Smoke and Lipopolysaccharides In Vivo - Mun-Ock Kim (Antioxidants, 2022)
Cigarette smoke (CS) is a risk factor that can induce airway enlargement, airway obstruction, and airway mucus hypersecretion. Although studies have shown that Korean black ginseng extract (BGE) has potent anti-inflammatory and antioxidant activities, the CS-induced inflammatory responses and molecular mechanisms are yet to be examined. The aim of this study was to examine the effect of BGE on the airway inflammatory response and its molecular mechanisms, using CS/lipopolysaccharides (LPS)-exposed animals and PMA-stimulated human airway epithelial NCI-H292 cells. The results show that BGE inhibited the recruitment of immune cells and the release of inflammatory mediators, such as tumor necrosis factor (TNF)-α and interleukin (IL)-6, monocyte chemoattractant protein (MCP)-1, elastase, and reactive oxygen species (ROS) in the airways of CS/LPS-exposed animals. BGE inhibited mucus secretion and the expression of Mucin 5AC (MUC5AC). Furthermore, BGE exhibited an anti-inflammatory effect by downregulating a signaling pathway mediated by transforming growth factor-β-activated kinase (TAK) 1, an important protein that accelerates inflammation by cigarette smoke (CS). Overall, the findings show that BGE inhibits lung inflammation and mucus secretion by decreasing the activation of TAK1 both in human epithelial cells and in CS/LPS-exposed animals, and could be a potential adjuvant in the treatment and prevention of airway inflammatory diseases caused by airway irritants such as CS.